Marine organisms in the strategies for combating corona viruses (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Despite the progress made in immunization and drug development, so far there are no prophylactic vaccines and effective therapies for many viral infections, including infections caused by corona viruses. In this regard, the search for new antiviral substances continues to be relevant, and the enormous potential of marine resources is a stimulus for the study of marine compounds with antiviral activity in experiments and clinical trials. The highly pathogenic human corona viruses-severe acute respiratory syndrome-related corona virus (SARS-CoV), Middle East respiratory syndrome corona virus (MERS-CoV), severe acute respiratory syndrome-related corona virus 2 (SARS-CoV-2) remain a serious threat to human health. In this study, the authors hope to bring the attention of researchers to the use of biologically active substances of marine origin as potential broad-spectrum antiviral agents targeting common cellular pathways and various stages of the life cycle of different viruses, including corona viruses. The research has been compiled using references from major databases such as Web of Science, PubMed, Scopus, Elsevier, Springer and Google Scholar (up to April 2021) and keywords such as ‘corona viruses’, ‘marine organisms’, ‘biologically active substances’, ‘antiviral drugs’, ‘SARS-CoV’, ‘MERS-CoV’, ‘SARS-CoV-2’, ‘3CLpro’, ‘TMPRSS2’, ‘ACE2’. After obtaining all reports from the databases, the papers were carefully analyzed in order to find data related to the topic of this research  (98 references). Biologically active substances of marine origin, such as flavonoids, phlorotannins, alkaloids, terpenoids, peptides, lectins, polysaccharides, lipids and others substances, can affect corona viruses at the stages of penetration and entry of the viral particle into the cell, replication of the viral nucleic acid and release of the virion from the cell; they also can act on the host's cellular targets. These natural compounds could be a vital resource in the fight against corona viruses.